If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -910a = 26a Solving -910a = 26a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-26a' to each side of the equation. -910a + -26a = 26a + -26a Combine like terms: -910a + -26a = -936a -936a = 26a + -26a Combine like terms: 26a + -26a = 0 -936a = 0 Divide each side by '-936'. a = 0 Simplifying a = 0
| Sin(15x)=15 | | 9y=9+27 | | 2(19-3a)=66-8a | | 2x^2+15x-50=22-x^2 | | 6(2+6b)-8(b+4)=-20 | | 66-8a=2(19-3a) | | (x^2-x)-14(x^2-x)+24=0 | | 2x+7=6x+31 | | y+8=0.5(x-3) | | 3w-12=-27 | | 2a^2=1+a | | (25x^2-100x+50)+(50x-50)(2x)-(20x)(5-5x)-50x^2=0 | | x-8=-3x+11 | | d(t)=(20+3t)t | | 2(2x+8)+4=4x+20 | | Y-1(12-2x)=6 | | 2x^2+7x-32=0 | | X+15=3x-75 | | 65-2c=-23 | | (30-1y)+1y=30 | | -140/21 | | -6x+10y=134 | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(-10x^2)=0 | | 180+7x=360 | | (20-2x)(10-2x)(x)= | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(10x^2)=0 | | 5c+3=29 | | 2x+2(x+6)=12 | | 3x^2-12x^2+36x=0 | | 4s-8=15 | | 2x^2-36x=720 | | 18+8x=88 |